2005
DOI: 10.1523/jneurosci.1531-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hippocampal Cav1.2 Ca2+Channels in NMDA Receptor-Independent Synaptic Plasticity and Spatial Memory

Abstract: Current knowledge about the molecular mechanisms of NMDA receptor (NMDAR)-independent long-term potentiation (LTP) in the hippocampus and its function for memory formation in the behaving animal is limited. NMDAR-independent LTP in the CA1 region is thought to require activity of postsynaptic L-type voltage-dependent Ca2+channels (Cav1.x), but the underlying channel isoform remains unknown. We evaluated the function of the Cav1.2 L-type Ca2+channel for spatial learning, synaptic plasticity, and triggering of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
357
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(393 citation statements)
references
References 77 publications
19
357
3
1
Order By: Relevance
“…CaMKII has been reported to stimulate the activity of recombinant CaV3.2 channels by phosphorylating the cytoplasmic linker connecting IIS6 to IIIS1 (24), but it had no effect on channel open time. Therefore, given the increasing importance of CaMKII, calcineurin, and dihydropyridine-sensitive calcium channels in neuronal plasticity and gene regulation (25)(26)(27)(28)(29), our hypothesis, which is consistent with newer structural data emphasizing the importance of the S6 helices in gating (30), provides a simple, testable mechanism for integrating many old and new observations on calcium channel regulation by calcium and reversible protein phosphorylation.…”
Section: Discussionsupporting
confidence: 82%
“…CaMKII has been reported to stimulate the activity of recombinant CaV3.2 channels by phosphorylating the cytoplasmic linker connecting IIS6 to IIIS1 (24), but it had no effect on channel open time. Therefore, given the increasing importance of CaMKII, calcineurin, and dihydropyridine-sensitive calcium channels in neuronal plasticity and gene regulation (25)(26)(27)(28)(29), our hypothesis, which is consistent with newer structural data emphasizing the importance of the S6 helices in gating (30), provides a simple, testable mechanism for integrating many old and new observations on calcium channel regulation by calcium and reversible protein phosphorylation.…”
Section: Discussionsupporting
confidence: 82%
“…It has been shown that the LTCC is involved in NMDA receptor-independent LTP and spatial memory formation in mouse behavioral tests (100). As predicted by this established role for the LTCC in LTP and memory formation, we found that long-term memory in mutant presenilin flies was specifically affected during recovery from stress.…”
Section: Discussionsupporting
confidence: 78%
“…These observations indicate that CACNA1C may play a role in NMDA receptor‐dependent signaling and in synaptic plasticity in the hippocampus. In addition to ASD, SNPs in CACNA1C gene are linked to psychiatric disorders including schizophrenia and bipolar disorder (Li et al., 2015; Moosmang et al., 2005). In a large GWAS, two genes encoding the α 1 subunit of calcium channel ( CACNA1C) and its regulatory β 2 subunit ( CACNB2) were strongly linked to psychiatric disorders and ASD (Cross‐Disorder Group of the Psychiatric Genomics Consortium, 2013).…”
Section: Reviewmentioning
confidence: 99%